Shaping Social Identities after Violent Conflict : Youth in the Western Balkans - Pratto, Felicia; Žeželj, Iris; Maloku, Edona; Turjacanin, Vladimir; Brankovic, Marija (Palgrave Macmillan, 2020)
Examines the identities of young adults in Bosnia-Herzegovina, Serbia, Kosovo, and Macedonia. With research drawn from a large multidisciplinary project exploring a potential for reconciliation in post-conflict societies, the authors discuss the interplay between ethnic, religious and national identities that have been the source of recent violent conflicts. They focus on people aged 18-30, representing generations that are socialized after the wars, but live in ethnically divided societies burdened with a difficult history. Another aim of the project was to compare majority and minority perspectives within each country, and to provide a unique view on how to reinterpret and build more inclusive social identities.